HOUSING PRICE BUBBLE: PENYEBABNYA DAN MASALAH YANG MUNCUL KARENANYA - Chandra Utama (Bina Ekonomi, 2012)
Housing price bubble is defined as continuous rising of house price that make the price above the fundamental value. Usually economic agents do not realize the bubble of housing price before it is burst. In period of price bubble, credits for houses increase dramatically because the values of houses, as collateral, climb gradually. The mortgage becomes interesting financial asset that give high return and low risk. The number of people wants to buy rise and demand for houses go up. The housing sector also pushes the growth of economy and financial sector significantly. The problems of housing price bubble spring up since the bursting of bubble and the price of house down. Many economic agents loss their money and many companies become bankruptcy. The financial system and economy also suffer from the burst of housing bubble. This paper defines 6 psychological and 6 economical aspects that cause the price bubble. Furthermore, it is also discuss the negative effect of the bursting. At last, the simple suggestion to avoid the housing price bubble is presented.Key words: housing price bubble, burst of bubble, mortgage.